Human immunodeficiency virus integrase protein requires a subterminal position of its viral DNA recognition sequence for efficient cleavage. - Vink, C (1991)
Retroviral integration requires cis-acting sequences at the termini of linear double-stranded viral DNA and a product of the retroviral pol gene, the integrase protein (IN). IN is required and sufficient for generation of recessed 3' termini of the viral DNA (the first step in proviral integration) and for integration of the recessed DNA species in vitro. Human immunodeficiency virus type 1 (HIV-1) IN, expressed in Escherichia coli, was purified to near homogeneity. The substrate sequence requirements for specific cleavage and integration of retroviral DNA were studied in a physical assay, using purified IN and short duplex oligonucleotides that correspond to the termini of HIV DNA. A few point mutations around the IN cleavage site substantially reduced cleavage; most other mutations did not have a drastic effect, suggesting that the sequence requirements are limited. The terminal 15 bp of the retroviral DNA were demonstrated to be sufficient for recognition by IN. Efficient specific cutting of the retroviral DNA by IN required that the cleavage site, the phosphodiester bond at the 3' side of a conserved CA-3' dinucleotide, be located two nucleotides away from the end of the viral DNA; however, low-efficiency cutting was observed when the cleavage site was located one, three, four, or five nucleotides away from the terminus of the double-stranded viral DNA. Increased cleavage by IN was detected when the nucleotides 3' of the CA-3' dinucleotide were present as single-stranded DNA. IN was found to have a strong preference for promoting integration into double-stranded rather than single-stranded DNA.